Присяга суддів як складова частина їх конституційно-правового статусу - Кравчук, В.; Kravchuk, V. (СНУ ім. Лесі Українки, 2018)
Стаття присвячена аналізу присяги суддів як елементу їх конституційно-правового статусу та визначенню її ролі для становлення конституційних основ правового статусу суддів. Визначено фактори, що зумовили необхідність правового регулювання інституту присяги суддів, а також охарактеризовано умови, в яких здійснювалось складення присяги суддями. Досліджено динаміку розвитку інституту присяги суддів в національному конституційному та судоустрійному законодавстві. Присяга суддів є додатковим (неосновним) структурним елементом їх правового статусу, за допомогою якого, особи, призначені на посади суддів, набувають повноважень суддів. The article analyzes the oath of judges as an element of their constitutional-legal status and emphasizes the importance of it for judges' legal status. The author describes the factors that determine the necessity of the legal regulation of the institute of judges' oath and the conditions under which the judges swear an oath. The study has revealed the dynamics of the institute of judges' oath development in the national constitutional and judicial legislation. The content-based analysis of the normative legal acts gives grounds to admit that the existing text of the oath is the most appropriate in its historical and legal aspects. However, the procedure of taking the oath should be more accurate and concrete. The author offers to fix the following provisions in the legislation: «Swearing the Ukrainian people, the judge must keep one hand on the Constitution of Ukraine and must personally speak out the oath». Such a procedure, in the author's opinion, will have a great psychological impact on the newly appointed judges, thus intensifying the judges' perception of the great responsibility and significance of their activities in administering justice.
Judges' Oath as an Integral Part of their Constitutional and Legal Status
Keywords: правовий статус; правовий статус судді; присяга; присяга судді; суддя; legal status; legal status of a judge; oath of a judge; oath; judge